The Impact of Gut Microbiota on Long COVID: Insights and Challenges.: The Impact of Gut Microbiota on Long COVID: Insights and Challenges. - Araujo-Filho, Irami; Meneses do Rêgo, Amália Cinthia (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2024)
Long COVID-19, characterized by persistent symptoms following acute COVID-19 infection, presents a multifaceted challenge. Recent research has unveiled the potential role of gut microbiota in shaping the course of Long COVID, offering insights into its consequences and therapeutic avenues. Dysbiosis in the gut microbiota, marked by a reduction in beneficial commensal bacteria and an increase in pro-inflammatory taxa, appears to be a common feature in Long-term COVID patients. Notably, microbiota composition correlates with symptom severity and duration, suggesting a link between gut microbiome composition and Long COVID's clinical manifestations. Various interventions, such as antibiotics, probiotics, and dietary modulation, have been explored as potential strategies to mitigate gut dysbiosis and its effects on Long-term COVID-19. Parallels between Long-term COVID and myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) have been drawn, indicating potential shared mechanisms, including gut microbiota involvement. Longitudinal studies highlight the persistence of gut microbiota alterations beyond the acute phase of COVID-19, emphasizing the need for long-term monitoring and interventions. While these findings offer promise, standardized and comprehensive research is essential to establish causality and elucidate the intricate mechanisms underlying the gut microbiota's influence on Long COVID. Understanding this relationship holds the potential to develop novel approaches for managing and improving Long COVID outcomes, addressing a pressing public health concern.